A methodology to compute the territorial productivity of scientists: The case of Italy. Issue 4 (October 2015) - Abramo, Giovanni; D'Angelo, Ciriaco Andrea
Highlights: We present a methodology to map the research productivity of scientists. The methodology is applied to the hard sciences in Italy. We rank by research productivity the fields of research for each territory. We rank by research productivity the territories in each field of research. Results are of interest to national and local policy-makers, and industry. Abstract: Policy-makers working at the national and regional levels could find the territorial mapping of research productivity by field to be useful in informing both research and industrial policy. Research-based private companies could also use such mapping for efficient selection in localizing R&D activities and university research collaborations. In this work we apply a bibliometric methodology for ranking by research productivity: (i) the fields of research for each territory (region and province); and (ii) the territories for each scientific field. The analysis is based on the 2008–2012 scientific output indexed in the Web of Science, by all professors on staff at Italian universities. The population is over 36, 000 professors, active in 192 fields and 9 disciplines.